Federation Management of Future internet - Dubey, Pritesh; Patel, Rakesh; Singh, Prateek Kumar (International Journal For Research In Advanced Computer Science And Engineering, 2016)
Internet is collection of network today internet is very important and very useful to every people. Because today every work is complete through internet and so management of future internet it is most important in future internet we use particular mobile wireless network and extra ordinary technology in this context - a changing business environment for telecommunications and the internet and the opportunities to provide future internet services. Technical perspective the limitations of the current internet technology are outlined. The research activities that address the challenge of Future internet research are introduced under three main lines: future internet architecture and Network technologies, Spectrumefficient access to future networks and converged infrastructures in support of future networks. Examples for first promising approaches to significantly change the principles of the internet architecture and protocols are presented.